2022
DOI: 10.36440/recmvz.v20i1.38315
|View full text |Cite
|
Sign up to set email alerts
|

Histerocele inguinal gravídica em gata: relato de caso

Abstract: A histerocele é uma condição rara na espécie felina, sendo caracterizada por protrusão do útero pelo anel inguinal. O diagnóstico diferencial inclui tumor mamário, linfadenopatia, hematoma, abscesso e granuloma. Assim, exames de imagem como a ultrassonografia abdominal apresentam importante papel no diagnóstico e prognóstico da doença. O tratamento dessa condição é cirúrgico e inclui a realização de herniorrafia e ovário-histerectomia, a fim de evitar recidivas e a transmissão hereditária. O presente trabalho … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…This suspicion is based on the fact that MH is the most common disease that can result from contraceptive administration in cats. Several authors have reported the occurrence of MH after the administration of contraceptives in female cats (Araújo et al, 2014;Loretti et al, 2005;Melo et al, 2021;Oliveira et al, 2014), strengthening the suspicion that the female cats in the study showed such alterations.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…This suspicion is based on the fact that MH is the most common disease that can result from contraceptive administration in cats. Several authors have reported the occurrence of MH after the administration of contraceptives in female cats (Araújo et al, 2014;Loretti et al, 2005;Melo et al, 2021;Oliveira et al, 2014), strengthening the suspicion that the female cats in the study showed such alterations.…”
Section: Resultsmentioning
confidence: 58%
“…In a previous case report, we found that a single application of medroxyprogesterone was sufficient to cause MH in a female cat (Oliveira et al, 2014). However, most articles published in the literature are case reports.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation